Gays picket Los Gatos Christian Church - Sahl, Ted (photographer):::Creator::::::::::::
Members of the Lesbian and Gay Association of Engineers and Scientists (LGAES) and supporters picket the Los Gatos Christian Church. Ed Sebesta, President of LGAES stands in the center between two women. Several of the protestors are holding signs.